2015
DOI: 10.1121/1.4919289
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical models for the acoustic response of a solids-loaded encapsulated bubble

Abstract: A method of active acoustic resonance interference spectroscopy is introduced for estimation of bubble properties. A modified form of Rayleigh-Plesset equation for forced oscillation of either a single free bubble or elastic shell encapsulated microbubble with attached solids loading is solved by the regular perturbation method for steady oscillatory solutions as a result of small amplitude acoustic excitation by a point sinusoidal oscillator. A model for the total pressure field at an acoustic receiver in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…We note that theoretically the mass loading from our NP shell is negligible. 28 Previous work also found that NP shell does not modify the acoustic properties of MMBs. 29 However, the resonant frequencies of MMBs with larger radii (435 μm) stabilized at approximately 50 kHz.…”
Section: Oscillating Microbubbles For Nanoparticle Release Y Gao Et Almentioning
confidence: 92%
“…We note that theoretically the mass loading from our NP shell is negligible. 28 Previous work also found that NP shell does not modify the acoustic properties of MMBs. 29 However, the resonant frequencies of MMBs with larger radii (435 μm) stabilized at approximately 50 kHz.…”
Section: Oscillating Microbubbles For Nanoparticle Release Y Gao Et Almentioning
confidence: 92%